Analisis Sistem Transmisi Pada Mobil Hemat Energi Asykar Prototype Gasoline Terhadap Konsumsi Bahan Bakar - Agustinus, Agustinus; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In design of a vehicle that is comfortable and safe while driving and to improve work performance on a vehicle, there are a number of things to consider, namely the steering system, brakes, suspension and transmission system. In this research, the writer will design and analyze the transmission system in Asykar Proto Gasolin Energy Saving Vehicle. The study began by searching for car specification data, Asykar Proto then calculating the center of gravity, then calculating the car speed at each gear ratio in the transmission system, measuring fuel consumption, calculating the mileage on each gear, calculating net traction force, designing the transmission system such as shafts, bearings, sprockets, chains and analysis. From this research, we will find what fuel consumption and distance can be achieved in 1 liter of fuel by Asykar Proto Gasolin Energy Saving Vehicle.Keywords : transmission system, Asykar Proto Gasolin Energy Saving Vehicle, car mileage in 1 litre of fuel